Effects of late defoliations on chemical and sensory characteristics of cv. Uva Longanesi wines - Tessarin, P.; Boliani, A. C. [UNESP]; Botelho, R. V.; Rusin, C.; Versari, A.; Parpinello, G. P.; Rombola, A. D. (Soc Chilena Ciencia Suelo, 2015)
In this study we investigated the effects of late leaf removal on the berry and wine composition and on wine sensory characteristics of Uva Longanesi, a late maturing red Italian grape variety, which wines are characterized by high levels of alcohol and excessive astringency, the latter apparently intensified by late defoliation practices. During 2008 season, spur-pruned trained vines were submitted to manual defoliation (4 basal leaves) at the onset (DEF I, 210 DOY) or at the end (DEF II, 231 DOY) of veraison and compared with non-defoliated plants (CON). On every DEF II vine, since defoliation until harvest, a cluster was shaded (DEF II + shading). A decrease of the berry soluble solids and skin anthocyanins was found in DEF I vines. Defoliation modified composition and sensory characteristics of wine with DEF II having higher alcohol strength and astringency compared to DEF I, whereas CON wines displayed intermediate values. The practice and timing of partial late defoliation greatly affected the chemical and sensory attributes of wine.
Keywords: Vitis vinifera; Grapevine; Leaf removal; Polyphenols; Sensory analysis